Akemetopon, a new genus containing three new species of planthoppers (Hemiptera: Fulgoroidea: Delphacidae) - Weglarz, Kathryn M.; Bartlett, Charles R. (Zootaxa, 2011)
The new delphacid genus Akemetopon gen. n. (Delphacinae: Delphacini) is described and illustrated with 3 new species from Arizona and Mexico: Akemetopon inornatum sp. n., A. politum sp. n., and A. ainigma sp. n. A key to species is provided. The barcoding portion of the mitochondrial gene Cytochrome Oxidase I (COI) was sequenced for A. politum sp. n. A maximum likelihood analysis places this genus in the basal Delphacini.